Assessing the Causes of Dedicated Revenues\' Fractions in Health Care Centers and Strategies to Reduce Them (A Qualitative Study) - Jafarsadegh Tabrizi; Saeideh Alidoost; Ahmad Mardi; Mostafa Farshi-khorsand; Mohammadali Rahmat (Tehran University of Medical Sciences, 2016)
Background: Lack of financial resources or their poor organization is one of the service delivery challenges and Fraction of dedicated revenues is significant problem in health centers in financial resources management. Hence, this study conducted to investigate causes of dedicated revenuechr('39')s fraction and strategies to reduce them. Materials and Methods: This qualitative study was carried out based on phenomenology approach in East Azerbaijan Province in 2014. Data collection methods were Focus Group Discussion (FGD) and semi-structure interview guide based which continued to saturation. their participants were selected using purposeful sampling method. Data were analyzed using content analysis method. Results: Based on participantschr('39') experiences, six themes were extracted for causes of fraction and strategies to reduce them. These themes included causes and strategies related to fractions per capita, insurance fractions, fractions related to sending documents, registration fractions, clientschr('39') deductions and fractions related to incomplete deposit of cash incomes. In general, eighteen causes and twenty three strategies were identified in dedicated revenues fractions.                                                                                                                        Conclusion: The causes of fractions were related to all stages of changing service process to revenue and insurance obligations in health care centers and strategies and identified interventions emphasize on mentioned fields.